Inhibition of pancreatic cancer stem cell characteristics by α‐Mangostin: Molecular mechanisms involving Sonic hedgehog and Nanog. Issue 4 (3rd February 2019) - Ma, Yiming; Yu, Wei; Shrivastava, Anju; Srivastava, Rakesh K.; Shankar, Sharmila
Abstract: The current investigation was intended to elucidate the molecular mechanism of α‐Mangostin in the regulation of pancreatic cancer stem cell (CSC) characteristics. Here, we demonstrate that α‐Mangostin inhibited cell proliferation in pancreatic CSCs and cancer cell lines while it showed no effect on human pancreatic normal ductal epithelial cells. Also, α‐Mangostin inhibited colony formation and induced apoptosis in these cells. Further, α‐Mangostin inhibited the self‐renewal capacity of CSCs isolated from human primary tumours and Kras G12D mice. Furthermore, α‐Mangostin inhibited the invasive and metastatic ability of pancreatic CSCs by suppressing the epithelial‐to‐mesenchymal transition (EMT) via up‐regulation of E‐cadherin and down‐regulation of mesenchymal phenotype by inhibiting N‐cadherin, Snail and Slug expression. Interestingly, the pluripotency maintaining factors and CSC markers were inhibited by α‐Mangostin thus suggesting that α‐Mangostin can target CSCs to inhibit pancreatic cancer effectively. Gli signalling plays a crucial role in the self‐renewal and pluripotency of CSCs. α‐Mangostin inhibited the Gli transcription and the expression of Gli target genes (Nanog, Oct4, c‐Myc, Sox‐2 and KLF4) in CSCs. Using ChIP assay, we demonstrated that Nanog could directly bind to promoters of Cdk2, Cdk6, FGF4, c‐Myc and α‐Mangostin inhibited Nanog binding to these promoters. Conversely, the inhibitory effects of the α‐Mangostin on CSC proliferation and Gli or Nanog transcription and their targets were abrogated by either enforced activation of sonic hedgehog (Shh) or by the overexpression of Nanog. Taken together, our studies suggest that α‐Mangostin may act as Gli inhibitor and establishes the pre‐clinical significance of α‐Mangostin for the prevention and treatment of pancreatic cancer.